Odpowiedź:
1.
[tex]1\frac{1}{2} :\frac{3}{7}:\frac{2}{7}= \frac{3}{2} *\frac{7}{3}*\frac{7}{2}=\frac{147}{12} =\frac{49}{4} =12 \frac{1}{4}[/tex]
odpowiedz: A
2.
[tex]1\frac{2}{3}-\frac{3}{5}+\frac{2}{5}=\frac{5}{3}-\frac{3}{5}+\frac{2}{5}=\frac{25}{15}-\frac{9}{15}+\frac{6}{15}= \frac{22}{15}}=1\frac{7}{15}[/tex]
odpowiedz: D
3. Nie widać całej treści zadania
4.
a) [tex]1\frac{3}{5} +\frac{1}{5} :\frac{10}{7}= \frac{8}{5}+\frac{1}{5}*\frac{7}{10}=\frac{8}{5}*\frac{7}{50}= \frac{28}{125}[/tex]
b)[tex](3\frac{2}{9} +\frac{1}{3} )*(\frac{3}{10} :\frac{1}{3})=(\frac{29}{9} +\frac{1}{3})*(\frac{3}{10}*3)= (\frac{29}{9} +\frac{3}{9})*\frac{9}{10} = \frac{32}{9}*\frac{9}{10}=\frac{32}{10}=3\frac{2}{10}=3\frac{1}{5}[/tex]
Szczegółowe wyjaśnienie: